EFISIENSI FAKTOR-FAKTOR PRODUKSI LEDRE PISANG DI UD. DUA PUTRI DEWI, KOTA MALANG - Sari Perwita R Ignatia (Fakultas Pertanian, 2020)
Banana Ledre is a food product processed from banana which is a type of snack. Processing of agricultural products aims to add value to this product because it can be sold at a higher price than fresh product. Banana ledre made by U.D. Dua Putri Dewi, Malang City uses several inputs other than banana as raw material. In the production process, efficiency in the use of inputs is an important thing that needs to be considered by entrepreneurs. Technical efficiency is a measure of how well resources or production inputs are used in the production process to provide optimal results. This study aims to analyze the technical efficiency of the use of production inputs consisting of raw materials, labor, and wages in producing banana ledre. The method used to analyze technical efficiency is Cobb Douglas production function regression analysis. In order to do the analysis, the production function is transformed into a linear model. The research hypothesis was tested by comparing the value of bi with a value range of 0-1. The results showed that the use of production cost factors was not efficient. This is based on the b1 value of 1.474 where this value is greater than 1. The use of working hours is inefficient based on the b2 value (-0.515) which is less than 0. The use of work wages is efficient based on the b3 value (0.059) which ranges from 0-1. Based on these results, entrepreneurs need to review the use of raw material costs and working hours in the production process. Things that can be done include finding raw material suppliers that offer lower prices and optimizing working hours as efficiently as possible.